The effectiveness of parent-based pivotal response treatment on social health and psychological well-being among mothers with autistic children - Alizadeh, Aysun; Khosrojavid, Mahnaz; Khanzadeh, Abbas Ali Hossein (Researcher Bulletin of Medical Sciences, 2018)
Introduction: Parents of children with autism are increasingly are considered as one of the primary source of intervention for their children, also there is an increasing demand for access to effective interventions for families who have children with autism. The aim of this study is to investigate the impact of parent-based pivotal response treatment (PRT) on social health (the amount of interaction a person has with their community) among mothers with autistic children. Methods: The present study is a semi-experimental research and its design consists of pretest, posttest with control group and a sample of 40 mothers with autistic children referring to the educational and rehabilitation center of Tehran and Karaj from fall to winter of 2016., participants were selected in two groups of control (20 people) and tested (20 people). To measure the independent variables in the pretest, post-test questionnaires, Reef psychological well-being and the social health of Keyes and Shapiro (short form) were used. The experimental group was trained for PRT during three months. Ultimately, the collected data were analyzed applying SPSS software via paired t-test and independent t-test method. Results: The results showed that there was significant increase in scales of social heath and psychological well-being in both experimental group and control group; but the increment was significantly higher in experimental group (P < 0.001; P < 0.023 respectively). Conclusion: According to benefits of parental intervention in treatment and importance of increasing therapy sessions for children with autism, it is recommended that this therapy method in conjunction with conventional methods is offered to parents of children with autism specially mothers.